The study of the optical activity of some S-derivatives 4-R-5-((((3-(pyridin-4-yl)-1H-1,2,4-triazole-5-yl)thio)methyl)-4H-1, 2,4-triazole-3-thiols - Ye. O. Karpun; S. O. Borsuk; L. I. Kucherenko; V. V. Parchenko (Zaporozhye State Medical University, 2022)
About half of the drugs currently produced are chiral compounds, and about 90 % of these compounds are sold as racemates, consisting of an equimolar mixture of two enantiomers. Although they have the same chemical structure, most of the optical isomers of chiral substances show marked differences in biological activity. It is known that the presence of a single asymmetric atom has become almost an integral part of advanced drug design. The aim of this work was to determine the angle of rotation of the polarization plane of solutions of some S-derivatives of 4-R-5-((((3-(pyridin-4-yl)-1H-1,2,4-triazole-5-yl)thio)methyl))-4H-1,2,4-triazole-3-thiols and the establishment of regularities between the structure of the studied molecules and their optical activity. Materials and methods. The subject of the study was 2-[5-R1-4R2-1,2,4-triazole-3-ylthio]-1-aryletanols. The study of the angle of rotation of the plane of polarization of solutions of newly synthesized compounds was carried out using an Atago AP-300 polarimeter and the DFU 2.2.7 physical-chemical analysis method "Optical rotation". Results. The results of the physical-chemical analysis were carried out that the studied compounds exhibit optical activity. The compound 1-((4-methyl-5-(((3-(pyridin-4-yl)-1H-1,2,4-triazole-5-yl)thio)methyl)-4H-1,2,4-triazole-3-yl)thio)-2-phenylethan-1-ol (+43° [deg∙g/cm3∙dm]). The only levorotatory substance was 1-(4-fluorophenyl)-2-((4-methyl-5-(((3-(pyridin-4-yl)-1H-1,2,4-triazole-5-yl)thio))methyl)-4H-1,2,4-triazole-3-yl)thio)ethan-1-ol with specific rotation [α]D20 = -43° [deg∙g/cm3∙dm]. Conclusions. Studies had shown that 1-(4-fluorophenyl)-2-((4-methyl-5-(((3-(pyridin-4-yl)-1H-1,2,4-triazole-5-yl))thio)methyl)-4H-1,2,4-triazole-3-yl)thio)ethan-1-ol was able to rotate the light polarization plane to the left, which was evidence of the advantage of the S-enantiomer in the racemic mixture, and therefore this compound was considerable interest for further preclinical research. Also, all other analyzed compounds behave as optical isomers.